Conditions for Fairness in Polygamy Permit Applications from the Perspective of Sangatta Religious Court Judges - Firdaus, Ahmad; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This article analyzes the concept of fairness as a fundamental requirement in polygamous marriages, particularly in the context of applying for polygamy permits, from the perspective of judges at the Sangatta Religious Court. The research employs a qualitative field study approach, with data collected directly from the Sangatta Religious Court through observations, in-depth interviews, and documentation. The study's informants consist of three judges from the court. To ensure the validity and reliability of the data, triangulation methods and reliability testing were applied. The findings reveal that the judges at the Sangatta Religious Court interpret fairness in polygamous marriages primarily in material terms. Fairness is seen as the husband's ability to meet the basic needs of each wife—such as food, clothing, housing, and equitable night shifts—in a proportional manner, tailored to each wife's needs. Emotional aspects such as love, affection, and attention are considered subjective and thus fall outside the domain of judicial assessment of fairness. Furthermore, the requirement to act fairly is a critical factor influencing the approval of polygamy applications. This requirement is often presented through a formal statement of fairness delivered in court, which becomes a key consideration for judges during the decision-making process. The court's decision is also supported by trial evidence, corroborated by written documentation, and guided by considerations of potential benefits or harms resulting from the polygamous marriage.